A NURSE SCHEDULING APPROACH BASED ON SET PAIR ANALYSIS - Zhou, Jianfeng; Fan, Yuyun; Zeng, Huazhi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
In practice, multiple sources of uncertainties are needed to be treated in nurse scheduling. The problem involves multiple conflicting objectives such as satisfying demand coverage requirements and maximizing nurses’ preferences subject to a variety of constraints imposed by legal regulations, personnel policies and many other hospital-specific requirements. The aim of this research is twofold: Firstly, to apply SPA (set pair analysis) theory to the nurse scheduling problem (NSP) to treat uncertainties and to model and solve the nurse schedule assessment problem. Secondly, to integrate the nurse schedule assessment model with GA (genetic algorithm) to establish a nurse scheduling approach. A case study of nurse scheduling in a surgical unit of Guangzhou Chest Hospital in China is presented to validate the approach.